Janamejaya’s Big Brother: New Light on the Mahabharata’s Frame Story - Brodbeck, Simon (Religions of South Asia, 2010)
This article explores the story of Pariksit in the Mahabharata and suggests an interpretation whereby Pariksit’s eldest son opted out of Pariksit’s patriline, preferring that of his mother. This interpretation is supported by reference to various similar stories within the Mahabharata and elsewhere. The article then suggests that several different Mahabharata characters may be seen as parallel representations of Pariksit’s eldest son. Finally, the article offers an explanation of the Mahabharata’s oblique narrative strategy and reflects on the implications of these interpretations for the study of the text as a whole.